2018
DOI: 10.1039/c7ja00402h
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the suitability of alkaline or enzymatic sample pre-treatment for characterization of silver nanoparticles in human tissue by single particle ICP-MS

Abstract: The method using enzymatic tissue treatment followed by spICP-MS is efficient for determination of mass and number concentration and size distribution of AgNPs in human placental tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In contrast, it was shown that enzymatic treatment with proteinase K was more suitable for silver nanoparticles in human placental tissue, as TMAH treatment appeared to change the nanoparticles, most likely by silver ion precipitation and/or nanoparticle aggregation. 280 Please do not adjust margins Please do not adjust margins…”
Section: Sample Preparationmentioning
confidence: 99%
“…In contrast, it was shown that enzymatic treatment with proteinase K was more suitable for silver nanoparticles in human placental tissue, as TMAH treatment appeared to change the nanoparticles, most likely by silver ion precipitation and/or nanoparticle aggregation. 280 Please do not adjust margins Please do not adjust margins…”
Section: Sample Preparationmentioning
confidence: 99%
“…This claim was drawn from published work with Au NP and not verified for NP with other compositions [33]. Caution must be used when employing enzymatic digestions for NP extraction from biological tissues due to the possibility for dissolution and possible reprecipitation [43]. Alcohols, such as methanol (MeOH), are used in a variety of organic compound extraction protocols from plant and animal tissues [44][45][46][47].…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Enzymatic digestion with Proteinase K at an enzyme concentration of around 4 µg Proteinase K per mg wet tissue resulted in a satisfactory size distribution but a 60% lower recovery rate of gold nanoparticles from rat spleen in comparison to alkaline digestion with tetramethyl ammonium hydroxide (TMAH) [17]. In contrast, silver nanoparticles were satisfactorily recovered from human placenta tissue at an enzyme concentration of 60 µg Proteinase K per mg wet tissue [18] and from chicken meat at an enzyme concentration of 4 µg Proteinase K per mg wet tissue [19]. Another study was able to make successful use of alkaline digestion for both gold and silver nanoparticle extraction from ground beef, Daphnia magna, and Lumbriculus variegatus [20].…”
Section: Introductionmentioning
confidence: 99%